Transformative Role of Epigenetics in Child Development Research: Commentary on the Special Section. Issue 1 (28th January 2016) - Keating, Daniel P.
Abstract : Lester, Conradt, and Marsit (2016) have assembled a set of articles that bring to readers of Child Development the scope and impact of the exponentially growing research on epigenetics and child development. This commentary aims to place this work in a broader context of theory and research by (a) providing a conceptual framework for developmental scientists who may be only moderately familiar with this emergent field; (b) considering these contributions in relation to the current status of work, highlighting its transformative nature; (c) suggesting cautions to keep in mind, while simultaneously clarifying that these do not undermine important new insights; and (d) identifying the prospects for future work that builds on the progress reflected in this special section.